2016
DOI: 10.1007/s00339-016-0291-5
|View full text |Cite
|
Sign up to set email alerts
|

Study of deposition parameters for the fabrication of ZnO thin films using femtosecond laser

Abstract: Femtosecond (fs) pulsed laser deposition (fs-PLD) of ZnO thin film on borosilicate glass substrates is reported in this work. The effect of important fs-PLD parameters like targetsubstrate distance, laser pulse energy, and substrate temperature on structure, morphology, optical transparency and luminescence of as deposited films is discussed.XRD analysis reveals that all the films grown using the laser energy range 120 J to 230 J are polycrystalline when they are deposited at room temperature in a ~ 10 -5 Torr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This was different to the approach of Hashmi et al, who studied the role of a dopant in the growth of ZnO films [63]. The laser source was the same as already used by the same group [61], while the dopant was samarium. The results indicated that with a Sm percentage of 1 wt %, the films retained the structure of crystalline ZnO with a preferential c-axis orientation, while for higher amounts of Sm, the formation of mixed oxides took place.…”
Section: Zinc Oxidementioning
confidence: 97%
See 1 more Smart Citation
“…This was different to the approach of Hashmi et al, who studied the role of a dopant in the growth of ZnO films [63]. The laser source was the same as already used by the same group [61], while the dopant was samarium. The results indicated that with a Sm percentage of 1 wt %, the films retained the structure of crystalline ZnO with a preferential c-axis orientation, while for higher amounts of Sm, the formation of mixed oxides took place.…”
Section: Zinc Oxidementioning
confidence: 97%
“…In the same year, Hashmi et al also studied the deposition of ZnO by fs PLD [61]. The laser source (Ti:sapphire) had a wavelength of 800 nm, a pulse duration of 100 fs and a repetition rate of 1 kHz.…”
Section: Zinc Oxidementioning
confidence: 99%
“…In our study these reasons are supported by XRD and AFM results which show that crystallite size is very small that increases number of grain boundaries. Furthermore, the samarium ions and atoms are also considered responsible for deep level emissions in SZO thin films because our previous work on undoped ZnO thin film using similar conditions of femto-PLD [21] did not show these VISIBLE range emission wavelengths.…”
Section: Photoluminescencementioning
confidence: 99%
“…Therefore a fs pulsed, regenerative amplified Ti:sapphire laser is used in the present research to fabricate samarium doped ZnO thin films at room temperature by using optimized PLD parameters [21]. Effect of samarium concentration on the structural, optical and electrical properties is investigated by analyzing the phase, topography, optical response, photoluminescence and electrical resistivity of these thin films.…”
Section: Introductionmentioning
confidence: 99%